Monte Carlo investigation on neutron dosimetry parameters of 252Cf Isotron brachytherapy source - Ahmadi, Ome Leila; Anbaran, Hossein Tavakoli (Penerbit Universiti Kebangsaan Malaysia, 2020)
In the present study, all dosimetry parameters around the 252Cf Isotron source for neutron brachytherapy were calculated. The 252Cf neutron energy spectrum was modeled using the Maxwellian spectrum. The calculations were performed using MCNPX.2.6.0 code based on the TG-43U1 protocol in the water medium. The neutron air kerma strength for the 252Cf Isotron source was computed as 0.3098 ± 0.0002 cGy cm2/μgh and the neutron dose rate constant was 6.559 ± 0.003 cGy/Uh. The anisotropy functions were calculated at intervals of 1, 2, 3, 4, and 5cm at different polar angles in the range of θ = 0̊ to 90º in respect to the source long axis in a water Phantom. The uncertainty of the calculated data at all distances is less than 1%. The radial dose function at different distances from the source for the Isotron model was compared with the theoretical HDR 252Cf source model. The discrepancies between the results were the highest at the distance of 0.5 cm, with relative differences of 5.64 %. For the 252Cf Isotron source, the data presented in this study provides better understanding on the dosimetric distribution of a theoretical neutron brachytherapy source, for potential clinical application.